Mechanically-foldable axial flow blood pump: response-surface-based structural optimization and hemolytic performance evaluation - Ji, Tairan; Jing, Teng; Cheng, Jianan (Frontiers in Physiology, 2025)
IntroductionTraditional percutaneous ventricular assist devices (PVADs) face limitations due to their small implantation size, requiring higher rotational speeds to meet left ventricular support demands. However, the elevated shear stress induced by high-speed operation leads to excessive hemolysis, necessitating design improvements for better clinical applicability.MethodThis study presents a foldable implantable blood pump featuring a collapsible flexible impeller and pump casing, which reduces its profile during implantation and expands to operational size at the target position, thereby allowing lower rotational speeds and improved hemolytic performance. Through numerical simulations combined with response surface methodology (RSM), we systematically analyzed the influence of various structural parameters on pump head and hemolysis index (HI), aiming at parametric optimization of the initial model for enhanced hydraulic efficiency and reduced blood trauma risk.ResultsSimulation analysis of seven parameter configurations identified five key structural parameters with dominant effects on head and HI: impeller inlet angle, impeller outlet angle, diffuser inlet angle, diffuser wrap angle, and impeller-diffuser gap. Using Box-Behnken Design (BBD), we established dual-response prediction models for both head and HI, analyzed significant interaction terms, and derived an optimized configuration achieving a 6.9% increase in head pressure and 17.9% reduction in HI compared to the initial design. Additional analysis revealed that increasing tip clearance reduces hemolysis at the cost of moderate head decrease.ConclusionWe designed and optimized a foldable axial-flow blood pump for transaortic implantation. The optimized configuration demonstrates a 6.9% head improvement to 2.346 m and 17.9% HI reduction to 1.081×10−2%. Furthermore, increasing tip clearance from 0.2  mm to 0.4 mm provides additional hemolysis reduction without excessively compromising the pressure head.